Pelatihan Peningkatan Kualitas Pengawas Internal Koperasi Provinsi Daerah Istimewa Yogyakarta - Irawan, Dandan (LPPM Universitas Koperasi Indonesia, 2024)
Supervision is the primary function of goal-oriented management. It is basically a comparison between actual performance and cooperative standards to ensure that the actions taken are correct. Every manager must supervise the activities of his subordinates. It can be defined as determining what has been achieved, deciding on performance, if necessary, implementing corrective actions so that performance conforms to the plan. Supervision is very important to achieve the goals of an organization. It is a process that allows management to implement its policies and take corrective action to improve performance if it does not meet predetermined standards. Planning is the beginning of the management process, while monitoring is said to be the final stage of the management process. While planning looks forward, Control looks backward. Supervision is impossible without planning, otherwise planning will mean nothing without supervision.